Detection of Babesia canis rossi, B. canis vogeli, and Hepatozoon canis in Dogs in a Village of Eastern Sudan by Using a Screening PCR and Sequencing Methodologies - Oyamada, Maremichi (American Society for Microbiology, 2005)
Babesia and Hepatozoon infections of dogs in a village of eastern Sudan were analyzed by using a single PCR and sequencing. Among 78 dogs, 5 were infected with Babesia canis rossi and 2 others were infected with B. canis vogeli. Thirty-three dogs were positive for Hepatozoon. Hepatozoon canis was detected by sequence analysis.